2014
DOI: 10.1038/srep03731
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment Plants as Chemical Observatories to Forecast Ecological and Human Health Risks of Manmade Chemicals

Abstract: Thousands of chemicals have been identified as contaminants of emerging concern (CECs), but prioritizing them concerning ecological and human health risks is challenging. We explored the use of sewage treatment plants as chemical observatories to conveniently identify persistent and bioaccumulative CECs, including toxic organohalides. Nationally representative samples of sewage sludge (biosolids) were analyzed for 231 CECs, of which 123 were detected. Ten of the top 11 most abundant CECs in biosolids were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 44 publications
(63 reference statements)
0
80
0
3
Order By: Relevance
“…In that study, SS samples were collected from 74 POTWs that employ secondary treatment or better in 2006/2007 [35]. Several pollutants have been analyzed 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 in these samples and the results have been published [29,[36][37][38][39]. However, no earlier study has reported the occurrence of bisphenols in SS from nationally representative samples.…”
Section: Introductionmentioning
confidence: 97%
“…In that study, SS samples were collected from 74 POTWs that employ secondary treatment or better in 2006/2007 [35]. Several pollutants have been analyzed 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 in these samples and the results have been published [29,[36][37][38][39]. However, no earlier study has reported the occurrence of bisphenols in SS from nationally representative samples.…”
Section: Introductionmentioning
confidence: 97%
“…(18) Moreover, retention times in anaerobic digesters are not long enough for significant biological transformation of TCC, yet the retention times are much longer than other unit operations providing bacteria a longer exposure time to adapt to TCC. (4,19,20) The objective of this research was to determine if TCC impacts the abundance of ARGs as well as the microbial community structure and function in anaerobic digesters. Lab-scale anaerobic digesters were operated for 110 days with concentrations ranging from the background TCC levels found in the seed biosolids to inhibitory TCC concentrations that were twice the maximum concentration reported in the nationwide biosolids survey.…”
Section: Introductionmentioning
confidence: 99%
“…PhACs in STP influents and, hence, effluents originate from a number of human sources including among others: the natural production and excretion of the PhAC (6); the release of the PhAC from facilities where it is manufactured (7); its clinical use within the community (8,9) and within hospitals (10); the disposal of the PhAC into landfills and its resulting presence in landfill leachates (11); the illicit use of the PhAC (12,13); and the clinical and/or illicit use of other drugs/ chemicals that are metabolized to the PhAC upon consumption by humans (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%